Novel Causative Variants in DYRK1A, KARS, and KAT6A Associated with Intellectual Disability and Additional Phenotypic Features - Murray, Clark R.; Abel, Samantha N.; McClure, Matthew B.; Foster, Joseph, II; Walke, Maria I.; Jayakar, Parul; Bademci, Guney; Tekin, Mustafa (Journal of Pediatric Genetics, 2017)
Patients with unclear patterns of developmental and cognitive delay may go years without a definitive diagnosis despite extensive testing due to overlapping phenotypes of many genetic disorders. In this study, we identified causative variants in DYRK1A, KARS, or KAT6A in four individuals with global developmental delay and various findings including microcephaly and sensorineural hearing loss using whole exome sequencing. We present the cognitive, neurologic, and physical findings of four individuals to expand the clinical knowledge of possible features of the phenotypes of three rare genetic disorders. Through this process, we provide support for the use of whole exome sequencing in the setting of severe, intellectual disability or in those in whom a genetic disorder is suspected despite initial negative testing.
Keywords: ataxia; hearing loss; intellectual disability; microcephaly; seizures